Success Rate of Endotracheal Intubation - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Direct laryngoscopy (DL) remains the most popular method of endotracheal intubation despite the availability of easier methods like intubating laryngeal mask airway (ILMA)—a blind intubation aid with a high success rate of intubation even when employed by novices.Aim:This study compared the overall success rate of intubation using ILMA and DL during elective surgeries requiring intubation.Study Design:This was a comparative randomized study.Patients and Methods:Following the institutional ethical approval, 86 American Society of Anaesthesiologists physical status (ASA) I and II patients were randomized into DL and ILMA groups. Each received intravenous fentanyl 2 μg/kg, glycopyrrolate 4 μg/kg, intravenous propofol 3 mg/kg, suxamethonium 2 mg/kg to a maximum of 100 mg. Intubation was with DL in the first group and ILMA in the second group. Anesthesia was maintained with isoflurane and muscle relaxation with atracurium. The overall success rate, the success rate at the first attempt of intubation, time for intubation, and airway complications were assessed.Statistical analysis:Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 21.0. The quantitative variables were analyzed using the Student’st-test and qualitative using the Chi-square test. APvalue less than 0.05 was considered significant.Results:The success at insertion was 100% in the DL group and 95.3% with ILMA at the first attempt (P= 0.15). The success rate of intubation at the first attempt was 100 and 79.1% in the DL and ILMA groups, respectively. The mean time for intubation was 19.93 ± 6.17 and 46.54 ± 11.63 s in DL and ILMA, respectively (P= 0.001). Six patients (14%) had airway complications in the ILMA group.Conclusion:The overall success rate of intubation via ILMA is comparable to that of DL. In patients with normal airways, DL remains a comparatively faster and easier technique to secure the airway with tracheal intubation than ILMA.